2024
DOI: 10.1002/fsn3.3946
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of bay laurel (Laurus nobilis L.) towards the gut microbiome in dextran sodium sulfate induced colitis animal models

Nazeha A. Khalil,
Nora A. ALFaris,
Jozaa Z. ALTamimi
et al.

Abstract: Bay laurel (Laurus nobilis L.) contains active antioxidative phenolic components that are beneficial to human health. However, none was examined and reported utilizing health effects related to inflammatory bowel diseases (IBD) mainly ulcerative colitis (UC) in correlation to gut microbiota (GM). Thus, the current study aimed to investigate the impacts of bay leaves on UC albino rats targeting on the GM composition and their metabolites production (i.e., short‐chain fatty acids; SCFAs) for improving the gut ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In vivo studies of the antibacterial activity of Caucasian medicinal plants are very limited. Thus, in vivo studies demonstrated that a 3% Laurus nobilis L. leaf-supplemented diet in ulcerative colitis rat models increased the population of Bifidobacteria and Lactobacillus and significantly inhibited the growth of Clostridium and sulfate-reducing bacteria [ 76 ]. A total alkaloid extract of P. harmala at a concentration of 300 μg/mL decreased brown rot symptoms on potato tubers caused by aerobic, Gram-negative R. solanacearum in vivo [ 77 ].…”
Section: Antimicrobial and Antifungal Activity Of Caucasian Medicinal...mentioning
confidence: 99%
“…In vivo studies of the antibacterial activity of Caucasian medicinal plants are very limited. Thus, in vivo studies demonstrated that a 3% Laurus nobilis L. leaf-supplemented diet in ulcerative colitis rat models increased the population of Bifidobacteria and Lactobacillus and significantly inhibited the growth of Clostridium and sulfate-reducing bacteria [ 76 ]. A total alkaloid extract of P. harmala at a concentration of 300 μg/mL decreased brown rot symptoms on potato tubers caused by aerobic, Gram-negative R. solanacearum in vivo [ 77 ].…”
Section: Antimicrobial and Antifungal Activity Of Caucasian Medicinal...mentioning
confidence: 99%